A quasi-monolithic phase-field description for orthotropic anisotropic fracture with adaptive mesh refinement and primal–dual active set method. (December 2021) - Noii, Nima; Fan, Meng; Wick, Thomas; Jin, Yan
Abstract: In this work, thermodynamically consistent phase-field fracture frameworks for transversely isotropic and orthotropic settings are proposed. We formulate an anisotropic crack phase-field via a penalization approach for each family of fibers. The resulting model is augmented with thermodynamical arguments and then carefully analyzed from a mechanical perspective. The fracture dissipation inequality to prevent crack healing is imposed via a primal–dual active set strategy. Predictor–corrector mesh adaptivity allows to work with small length-scale parameters at a reasonable computational cost. Due to the importance of laminated structures for industrial applications, fracture responses for transversely isotropic and orthotropic materials are performed. Therein, several studies are conducted that include comparisons of anisotropic formulations with Griffith's critical elastic energy release rate and with specific critical fracture energy formulations, as well as non-split and split approaches. Highlights: Anisotropic crack phase-field formulation. Orthotropic materials with two families of fibers. Consistent additive split for the bulk anisotropic contribution. Analysis for the thermodynamical consistency. Formulation within a quasi-monolithic approach with predictor–corrector adaptivity.